Progressive impairment of directional and spatially precise trajectories by TgF344-Alzheimer's disease rats in the Morris Water Task. Issue 1 (December 2018) - Berkowitz, Laura; Harvey, Ryan; Drake, Emma; Thompson, Shannon; Clark, Benjamin
Abstract Spatial navigation is impaired in early stages of Alzheimer's disease, and may be a defining behavioral marker of preclinical AD. A new rat model (TgF344-AD) of AD overcomes many limitations of other rodent models, though spatial navigation has not been comprehensively assessed. Using the hidden and cued platform variants of the Morris water task, a longitudinal assessment of spatial navigation was conducted on TgF344-AD (n = 16) and Fischer 344 (n = 12) male and female rats at three age ranges: 4 to 5 months, 7 to 8, and 10 to 11 months of age. TgF344-AD rats exhibited largely intact navigation at 4–5 months, with deficits in the hidden platform task emerging at 7–8 months and becoming significantly pronounced at 10–11 months of age. In general, TgF344-AD rats displayed less accurate swim trajectories to the platform and searched a wider area around the platform region compared to wildtype rats. Impaired navigation occurred in the absence of deficits in acquiring the procedural task demands or navigation to the cued platform location. Together, the results indicate that TgF344-AD rats exhibit comparable navigational deficits to those found in individuals with preclinical-AD.